Before and after the K/Pg extinction in West Antarctica: New marine fish records from Marambio (Seymour) Island - Cione, Alberto Luis (2018)
An ichthyofauna recovered from the L opez de Bertodano Formation at Units 9 (uppermost Maastrichtian) and 10 (lowermost Danian) and the Sobral Formation (Danian), in Marambio (Seymour) Island in the James Ross Basin is described and analyzed herein. A review of previously described taxa based on the new material and several new fish records for the L opez de Bertodano Formation is provided, including the youngest record of Enchodus and the first Cretaceous evidence of Pachycormiformes.We also identify the first Paleocene fishes for the continent. The new information and the reinterpretation of previous Cretaceous records show that there was no decline in fish diversity until the CretaceousePaleogene (K/ Pg) boundary in the area and extinction event appears to have been rapid. Finally, we find that the distribution of some chondrichthyans and teleosts in the James Ross Basin appears to be climatically determined.